2012
DOI: 10.19030/jabr.v28i2.6842
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants Of Web-Based Investor Relations Activities By Companies Operating In Emerging Economies: The Case Of Jordan

Abstract: Using a multi-theoretical approach, this study seeks to examine the determinants of corporate web-based investor relations (IR) activities for companies listed on Amman Stock Exchange. Jordan provides an interesting context to pursue the objectives of this study because it provides insights into how listed companies are voluntarily responding to recent government and financial market regulators' initiatives to encourage the use of the internet and to keep financial market participants informed about corporate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 54 publications
1
36
1
Order By: Relevance
“…Some studies had reported a negative relationship between higher government agencies' ownership and website information disclosure. Other studies (Kelton & Yang, 2008;AbuGhazaleh, Qasim, & Roberts, 2012) demonstrated that there was a positive and significant relationship between government ownership and the IFR. Although the role of government ownership is substantial in the GCC countries (Al-Khouri, 2012), its impact on the IFR disclosure has not been thoroughly explored.…”
Section: Government Ownership and Ifrmentioning
confidence: 92%
See 2 more Smart Citations
“…Some studies had reported a negative relationship between higher government agencies' ownership and website information disclosure. Other studies (Kelton & Yang, 2008;AbuGhazaleh, Qasim, & Roberts, 2012) demonstrated that there was a positive and significant relationship between government ownership and the IFR. Although the role of government ownership is substantial in the GCC countries (Al-Khouri, 2012), its impact on the IFR disclosure has not been thoroughly explored.…”
Section: Government Ownership and Ifrmentioning
confidence: 92%
“…The GCC stock exchanges require the disclosure of ownership for each individual, corporation or government that owns 5 per cent or more (Al-Shammari, Brown, & Tarca, 2008). Following the approach used by Chahine (2007), AbuGhazaleh et al (2012) and Al-Musalli and Ku Ismail (2012), we likewise employed the aggregate proportion of ordinary shares (5 per cent or more) owned by substantial shareholders of these groups, as disclosed in the annual reports at the end of 2012.…”
Section: The Research Models and Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative relationship between company's age and disclosure of meaningful to the investors financial information provided on the Internet was found by AbuGhazaleh et al (2012). While research of Hossain et al (2012) didn't reveal that kind of relationship.…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 95%
“…Moreover, according to the signal theory, managers of large companies are more incited to proclaim the quality of their business to investors through voluntary disclosure. According to innovation diffusion theory, larger companies can better afford innovations and are more likely to have the necessary technological and personal resources (Flanagin, 2000; Abughazaleh et al 2012).…”
Section: Sizementioning
confidence: 99%